The Analysis & Exploration of Emotional Attachment in Video Game Character Design: A Case Study of Life is Strange - Ananda Saputra, Irgie; Januarsa, Aditya (Bina Nusantara University, 2025)
Character design in video games plays a crucial role in shaping players’ emotional engagement and long-term attachment to the characters they control and interact with. Narrative-driven games, in particular, rely heavily on visual aesthetics, personality construction, and moral agency to create emotionally resonant experiences. Life is Strange is selected as a case study due to its strong emphasis on character-centered storytelling, where the main character is developed through complex personal traits, emotional vulnerability, and narrative events that evolve according to players’ moral choices. These elements allow players to experience fluctuating emotional states throughout the gameplay. This study adopts a qualitative research approach to examine how visual character design and narrative structures contribute to the formation of emotional attachment, focusing specifically on teenage players in Indonesia. Data were collected through visual content analysis of the game’s character design and in-depth interviews with players to explore their emotional responses and interpretative experiences. The findings indicate that effective character design not only enhances emotional immersion but also enables players to recognize, express, and reflect upon their own emotions by relating in-game decisions to real-life experiences. Moral decision-making mechanics further strengthen this connection by positioning players as active participants in the character’s emotional journey. The conclusions of this study provide valuable insights for game developers and character designers, particularly in understanding how visual storytelling and narrative coherence can be strategically employed to foster emotional resonance and meaningful player–character relationships in narrative-driven video games.